Comparative Evolution of Animal and Human Coronaviruses, their Varieties and Virulence - Rustamani, Shabnam (Journal of Liaquat University of Medical & Health Sciences, 2021)
Coronaviruses are a group of enveloped viruses with single-stranded and RNA genomes that cause a wide-ranging spectrum of animal and human diseases. Initially, the pneumonia sort of disease was found in the Wuhan city of China, which later was identified as the novel coronavirus in November 2019. Recent studies have shown that HCOV, 229E, and OC43 develop flu-like symptoms which cause mild illness. This virus has then been declared a pandemic for its spread to several countries. Several types of research suggest that these were the birds and animals i-e bats and pangolins, which caused this virus to spread to humans. Human coronavirus has been attacking humans since 1962 by making changes in itself. However, Novel coronavirus has been proven to be a wide-spreading one. The SARSCOV is the most recent MERS-COV confirming that the coronavirus causes severe respiratory diseases, including fever and the common cold. As COVID-19 is pandemic worldwide, it primarily affects upper respiratory tracts (nose and throat), later on, infects lower respiratory tracts (lungs), and leads to pneumonia. SARS-COV-2 and MERS-COV2 are animal species that infect humans, causing severe illness. The reason behind this is that animal species can replicate at 37°C. The objective of the study is to collect reports from various databases for analysis. Globally, researchers have warned against the further spreading of the virus. If not controlled, this can result in more deaths and leave long-lasting consequences on global health and the economy. As compared with earlier episodes of SARS and MERS, the novel corona is more dangerous. Vaccination is required for future prevention against COV-19. KEYWORDS: Coronavirus, pandemic, Chiroptera, Respiratory infection, SARS.